Effect of photostimulation on biopotentials of maize leaves in conditions of thermal irritation - M. P. Motsnyj; О. V. Elina; N. P. Botsva; S. O. Kochubey (Regulatory Mechanisms in Biosystems, 2018)
Plant biopotentials can be used to evaluate their functional state and mechanisms for adaptation to changes in external conditions of their cultivation. The paper is devoted to the experimental study of the dynamics of total potential of maize leaves caused by cold and heat stimuli on the background of photopotential during continuous light stimulation. In the experiments, a specially designed stimulator was used that allowed simultaneous exposure of the plant to light and to thermal irritation. Studies have shown that background continuous light stimulation with white light with a brightness of 250 lux results in an increase in the amplitude of total action potentials caused by rhythmic cold stimulation. The amplitudes of "cold" potentials grew synchronously with the growth of the potential of hyperpolarization under the influence of photostimulation. With the termination of light stimulation, the amplitude of "cold" potentials stabilized. It is assumed that this effect is due to an increase in the amplitude of potentials of action, which correspond to the total potential due to the hyperpolarization of the membranes of the cells that generate them. Such hyperpolarization is due to an increase in the active transport of H+ ions through the membrane of cells in the light phase of photosynthesis. It has been shown that during pulsed heat stimulation, the preliminary continuous background light stimulation results in a decrease in the amplitude of "heat" potentials, a reduction in their duration, and the appearance of a short latent hyperpolarization potential in their initial phase. It is established that these changes correlate with the growth of the potential of hyperpolarization caused by background light stimulation. Based on the analysis of the detected changes, it was deduced that an increase in the level of hyperpolarization increases the threshold of excitability of cell membranes generating these potentials. When the photostimulation was switched off, the level of hyperpolarization decreased, but the amplitudes of the "heat" potentials increased. At the same time, the duration of the potentials increased sharply, and the elements characteristic of the variable potentials appeared in them. This may indicate a significant increase in sensitivity to heat irritation with a decrease in the level of hyperpolarization.